Antioxidant Potential of New Methyl-4-hydroxy-2H- 1,2-benzothiazine-3-carboxylate-1,1-dioxide Derivatives - Nadeem Arshad, Muhammad; Ullah Khan, Islam; Zia-Ur-Rehman, Muhammad; Shafiq, Muhammad (Asian Journal of Chemistry, 2011)
An easy synthesis of a series of N-alkyl-1,2-benzothiazine-1,1-dioxide derivatives from commercially available saccharine is reported in order to explore their antioxidant potential. The newly synthesized compounds were characterized by spectroscopic techniques (FT-IR, NMR, MS) and single crystal X-ray diffraction analyses. All the synthesized compounds were screened for their DPPH and FRAP analyses to determine their antioxidant activity.